Dormitory Distinction and Integration of ‎Islamic Education Basic Values in “Kampung ‎Inggris” Pare - Helfi (TADRIS: Jurnal Pendidikan Islam, 2022)
Various language course institutions in Indonesia are more focused on business oriented and ignore cultural values. Unlike the language institutions in Pare, Kediri, the dichotomy of material and moral values ​​is actually dissolved in local language institutions. The focus of this research was to portray the existence of reduction of Islamic value in the course institutions in Kampung Inggris (English Village), Pare, Kediri. Especially, additional activities carried out in the dormitory of the courses by assimilating lokal of Nahdlatul Ulama (an Islamic organization in Indonesia) traditions with the needs of language institutions. This research was conducted in the form of qualitative research by conducting observations and interviews. Interviews were conducted in the form of deep interviews to obtain broader and deeper data. Data collection was also carried out by involving the researcher directly and actively as an outsider in activities carried out by local communities assimilating to the agenda of the lokal course institutions. The result is that lokal culture in the form of values ​​and norms contributes to its own uniqueness in Kampung Inggris that are not found in other course institutions of other regions. These activities are accepted and applied in lokal course institutions with agendas such as tahlilan (ritual of salvation), islamic congregational prayer, diba'an ( prayer to God and Prophet) and so on.